Corporate trade credit and inventories: New evidence of a trade-off from accounts payable and receivable - Bougheas, Spiros; Mateut, Simona; Mizen, Paul (Journal of Banking & Finance, 2009)
Trade credit is an important source of finance for firms and has been well researched, but the focus has been on financial trade-offs. In this paper, we consider the trade-offs with inventories and develop a simple model that recognizes the incentives a firm faces to offer and receive trade credit. Our model identifies the response of accounts payable and accounts receivable to changes in the cost of inventories, profitability, risk and liquidity, and importantly, this influence operates through a production channel. Our results support the model and complement many existing studies focused on explaining the financial terms of trade credit.